Effect of the Argument-Driven Inquiry (ADI) Learning Model on Improving Students Argumentation Abilities - Indrawati Tahir; Abdul Haris Odja; Dewi Diana Paramata (Jurnal Pijar MIPA, 2026)
The Argument-Driven Inquiry (ADI) learning model is designed to provide students with opportunities to improve their methods of data collection, investigation, writing, answering investigative questions, and critical thinking. The ADI model also allows participants to participate in scientific debates and peer review. This study used a quasi-experimental one-group pretest-posttest design. Data were collected through a pretest and posttest comprising 10 essay questions, which were validated by expert lecturers and tested for validity and reliability. The data obtained from the tests were analyzed using test statistics, namely the Kolmogorov-Smirnov normality test, hypothesis testing, and n-gain analysis. The results showed that the average posttest scores in the experimental class across replications 1 and 2 were 84.5 and 83.7, respectively. Analysis using a t-test confirmed that the argumentation ability of class XI MAN 1 Boalemo students on the sound wave material taught using the Argument Driven Inquiry (ADI) model was significantly higher than the KKM of 70. The magnitude of the influence of the use of the Argument Driven Inquiry (ADI) model was also shown by the course average normalized gain per class, with the magnitude of the gain of the three classes consistently being in the high category, namely 0.77 for the experimental class, 0.77 for replication class 1, and 0.76 for replication class 2. The statistical test in this study shows that the calculated t-value (thitung) exceeds the critical t-value (ttabel) at the 5% significance level. This indicates a significant difference between students’ pre-test and post-test argumentation skills. These findings are consistent with various previous studies.